The investments of Brazilian pension funds in the commercial real estate market: a property portfolio analysis and its territorial pattern - Magnani, Maira (ANPUR, 2021)
Considering the need to understand financial and urban agents more attentively, in this article we propose to examine the condition of real estate investors of Brazilian pension funds. To this end, we examine the pension funds’ real estate portfolio, review the recent discussions involving the agent's investment in this asset class and address the regulatory aspects surrounding these practices and allocations. We also sought to characterize the real estate assets of pension funds: what are the main investment channels used, as well as the segments and sites invested. We concluded that there are new movements in favor of real estate investments conducted through financial vehicles, but that these investments, however, have characteristics very similar to those acquired through the direct purchase of commercial real estate. Both investment channels, as shown in the article, result in real estate for commercial use (such as shopping malls and offices) and are located in the states whose commercial real estate market is better developed, São Paulo and Rio de Janeiro.